The relationship between the glory of YHWH and the spirit of YHWH in Ezekiel 33 - 48 - Vries, P. de 1956- (2015)
Ezekiel is not only the prophet of the glory of YHWH but also of the Spirit of YHWH. What is the relationship between these two concepts? I restrict myself in this article to the last part of Ezekiel (33 - 48). In this final part of the book, we see how the Spirit of YHWH, who transforms and revives Israel, paves the way for the return of the glory of YHWH portrayed in the last vision. In the final vision, we read of a stream of water flowing from the temple. The water starts from the place where the פבֿרד of YHWH is present. This water must be related to the Spirit of YHWH. Not only the people but also the land is transformed. The message of the transformation of a community by the Spirit of YHWH is followed by the final vision where the glory of YHWH is evidently present in the sanctuary and even the land itself is transformed by the Spirit of YHWH; this is the climax of the message of Ezekiel. The presence of the לזּת of YHWH in the hearts and lives of the people of Israel is closely related to the presence of the פבֿרד of YHWH in the sanctuary. All is summarized in the name of the city: YHWH is there.
Keywords: Ezekiel; Glory of YHWH; Hypostasis; Spirit of YHWH; Temple vision